(untitled) (Eurasian Journal of Humanities and Social Sciences, 2026)
The following article analyzes the content, structure, and functions of national and religious consciousness, as well as their role in the spiritual culture of society, from a sociophilosophical perspective. National consciousness is illuminated as a form of social consciousness that expresses an individual’s awareness of their national identity and their attitude toward historical memory, language, customs, and cultural heritage. Religious consciousness is considered as a spiritual phenomenon that shapes human perceptions of divinity, moral values, and the meaning of life. Furthermore, the article reveals the cognitive, value-ethical, emotional, and practical components of national and religious consciousness, and substantiates their identification, integrative, educational, regulatory, and communicative functions. It also analyzes the role of these forms of consciousness in the spiritual stability of society, the preservation of cultural heritage, and the spiritual maturity of the individual.